APPARENT DIGESTIBILITY COEFFICIENTS OF DIFFERENT PROCESSED AFRICAN LOCUST BEAN (Parkia biglobosa) SEED MEAL BY Clarias gariepinus FINGERLINGS - ABDULLAHI, U. U; MAGAWATA, I.; UMORU, E. I.; YAHYA, M. A.; BAWA, D. Y.; ABRAHAM, O. V. (Nigerian Journal of Fisheries, 2021)
This study investigates the apparent digestibility coefficient of different processed African locust bean seed meal by Clarias gariepinus fingerlings. Diets containing 40% crude protein were formulated with Chromic oxide (Cr203) use as an inert marker at 1% inclusion in the reference and experimental diets. The five experimental diets containing 70% reference diets and 30% of the test diets. All data were subjected to a one-way analysis of variance. The Apparent Digestibility coefficient (ADC) values protein were significantly highest in fish fed diet II and III with 80.764±0.012 and 81.175±0.091 and lower in fish fed diet IV with 71.613±0.095. ADCs fat was significantly highest in fish fed diet II with 83.619±0.026 and lowest in fish fed diet I with 75.732±0.101. ADCs gross energy was significantly higher in fish fed diet II with 76.896±0.084 and lower I fish fed diet 71.138±0.084. ADCs calcium was significantly higher in fish fed diet V with 87.497±0.430 and lower in fish fed diet with 83.171±0.402. ADCs values for phosphorus were significantly higher in fish fed V with 90.122±0.087 and lowest in fish fed diet I with 87.154±0.237. In conclusion, the processed Parkia bigblobosa seed meal was digested, and they can be used as a partial protein source for Clarias gariepinus diets Keywords: , , ,